EXAMINING UNIVERSITY STUDENTS' SPEAKING SKILL THROUGH PARTICIPATION IN ENGLISH MEETINGS CLUB - A. Nur Aqidah Arrazzak. H; Andi Anto Patak; Fitriyani (International Journal of Business English and Communication, 2026)
This research examines the impact of participation in the English Meeting Club on the speaking skills of university students. In the context of foreign language learning, especially in Indonesia, English clubs serve as practical platforms for students to improve their communication competence outside the formal classroom setting. This study adopts a qualitative method with a case study approach to explore how students develop their speaking performance through engagement in club activities, specifically at Al-Markaz for Khudi Enlightening Studies (MAKES) in Makassar. Data were collected through semi-structured interviews with four active participants and analyzed using thematic analysis. The findings reveal significant improvements in five key components of speaking skills: comprehension, grammar, vocabulary, pronunciation, and fluency. Participants also reported increased confidence, clearer sentence structure, and more fluent expression, both during club discussions and in external academic or social contexts. The research highlights that peer support, frequent practice, structured discussions, and exposure to varied topics are essential factors that contribute to students’ speaking development. This study provides valuable insights into how English clubs can enhance language learning and suggests directions for future research by addressing sample and methodological gaps.